Impact of Integrated Reproductive Health Module Implementation on Junior High School Student Behavior Changes - Dini Saraswati Handayani; Ariyati Mandiri; Irna Kurnia Aprillani (Universitas Islam Bandung, 2019)
Socio-cultural changes, low understanding of religion, development of information technology, and limitation of appropriate information sources, causes sexual and reproductive behavior problems in adolescents. The solutions are through the application of an integrated reproductive health module as a teaching guide for teachers by using student center learning approach. The objectives of this study are to analyze the implementation effect of an integrated reproductive health module on changes in student behavior. This study using a quasi-experimental pretest-posttest design with control groups, which conducted from March to May 2017. The subject in this research is the students of class VII in 5 (five) Bandung city areas by inclusion and exclusion criteria. A total of 36 students from the five junior secondary schools as the research group received an integrated learning module, while 38 students from different classes in the same school as the control group using the reproductive health module based on the 2013 Curriculum. The data collection used questionnaires to assess behavior based on self-assessment, friends, and parents. The results of this study indicate that the interpersonal communication behavior increased by 5.74%, reproductive health behavior increased by 18.65%, and sexual behavior increased by 9.07%, with a significant difference compared to students who received the 2013 Curriculum (p<0.001). In conclusion, the implementation of the integrated reproductive health module had affected the student behavior change in maintaining reproductive health, sexual, and interpersonal communication. PENGARUH PENERAPAN MODUL PEMBELAJARAN KESEHATAN REPRODUKSI TERINTEGRASI TERHADAP PERUBAHAN PERILAKU SISWA SEKOLAH MENENGAH PERTAMAPerubahan sosial budaya, pemahaman agama yang rendah, perkembangan teknologi informasi, dan keterbatasan sumber informasi yang tepat menyebabkan permasalahan perilaku seksual dan kesehatan reproduksi pada remaja. Salah satu upaya yang dilakukan adalah melalui penerapan modul kesehatan reproduksi terintegrasi sebagai pedoman mengajar bagi guru dengan menggunakan pendekatan student center learning. Tujuan penelitian ini menganalisis pengaruh implementasi modul pembelajaran kesehatan reproduksi terintegrasi terhadap perubahan perilaku siswa. Penelitian ini menggunakan quasi-experimental pretest-posttest design with control groups yang dilakukan dari bulan Maret hingga Mei 2017. Subjek penelitian adalah siswa kelas VII di 5 (lima) wilayah Kota Bandung dengan kriteria inklusi dan eksklusi. Sebanyak 36 siswa dari lima sekolah menengah pertama sebagai kelompok perlakuan mendapatkan modul kesehatan reproduksi terintegrasi dan 38 siswa dari kelas yang berbeda di sekolah yang sama sebagai kelompok kontrol menggunakan materi kesehatan reproduksi berdasar atas Kurikulum 2013. Pengumpulan data menggunakan kuesioner penilaian perilaku oleh diri sendiri, teman, dan orangtua. Hasil menunjukkan bahwa perilaku komunikasi interpersonal siswa meningkat 5,74%, perilaku menjaga kesehatan reproduksi meningkat 18,65%, dan perilaku seksual sehat siswa meningkat 9,07% dengan perbedaan yang signifikan dibanding dengan siswa yang mendapatkan Kurikulum 2013 (p<0,001). Simpulan, penerapan modul pembelajaran kesehatan reproduksi terintegrasi berpengaruh terhadap perubahan perilaku kesehatan reproduksi siswa.